A new species of Anthurium Sect. Leptanthurium from Colombian Amazonia - López–Floriano, Oscar Mauricio; Croat, Thomas B.; Correa-Munera, Marco A. (Phytotaxa, 2022)
A new species of Anthurium sect. Leptanthurium is described and illustrated. It is compared with A. miritiparanaense, another endemic to the Colombian Amazonia as well as to A. raphaelense from Ecuador.